THEORIZATION ON THE DIDACTIC WAYS OF THE MODERN AFTER-SCHOOL EDUCATION - Mohilevska, Viktoriia (Educological discourse, 2018)
Summary. The author is of the opinion that existing researches on the didactic principles of the modern after-school education is not sufficient to be a benchmark in the practical activities of after-school institutions. She observes the need for their renewal, which is primarily due to the recognition of the after-school education by the state as an integral part of a continuous education system. The author sees the problem in the insufficient theoretical and methodological substantiation of the subject and the nature of the changes and the lack of new views on the modern educational process in the after-school environment. Therewith, according to the author, the changes also affect the transition of after-school educational activities to the competence paradigm, which became the benchmark for the national education system. Domestic researchers have doted many i’s on this problem. The theoretical and methodological approaches proposed by them to the implementation of the competence paradigm constitute a significant theoretical basis, which allows us to find answers to a number of topical issues of the given problem. But practice revealed the low level of the problem awareness at the level of the teaching staff. There is a need to continue researches on the content of the work of after-school establishments, as well as in the development of a methodology of modern means and methods of training that provide the formation of key competencies of pupils. In her discourse, the author emphasizes that modern pedagogy, responding to the challenges of time, also undergoes changes. Today, its new branches occur. The author suggests adding to the existing branches one more so-called pedagogy of leisure, the subject of which will be the development of a creative person in his free time, which is connected with the use of another balance of teaching methods and techniques than those used in the system of formal education. The author describes the concept of «content upgrading» in the context of a competent approach as changes starting with a new vision of the goals and objectives of learning, tools for constructing subject-subject relations, as well as technologies aimed at building vital competencies in pupils in after-school institutions. New effective requirements for classroom didactics require changes in the role and nature of learning activities. Nowadays foreign experience shows such examples. Domestic science should make this problem the subject of its further scientific researches.